Prevalence and antimicrobial resistance of Salmonella enterica isolated from cattle farms in Inner Mongolia - Mengyuan Xie; Yexin Chen; Hewei Shang; Xiuling He; Xiaojing Xu (BMC Veterinary Research)
Abstract Background Salmonella poses a significant health threat to both humans and animals owing to the emergence of antimicrobial-resistant strains. There are no studies on the incidence patterns of salmonellosis and multidrug-resistant Salmonella strains in Inner Mongolia, China's milk and beef-producing hotspot. Farms in Inner Mongolia, China, were randomly selected, and rectal swabs (600) and milk samples (757) were collected for isolation and identification of Salmonella, and antimicrobial resistance was assessed according to CLSI and NARMS guidelines. Twenty-one resistance genes from seven classes of antibiotics were selected for detection using polymerase chain reaction (PCR), and Salmonella-NMGS9 was selected for whole genome sequencing and drug resistance gene prediction analysis. Results Salmonella was found in 24 (85.71%) of the 28 large-scale cattle farms in Inner Mongolia, China, resulting in 176 Salmonella strains from 1357 samples (with a prevalence of 3.88%). Of the 158 strains tested for their susceptibility to 19 antibiotics, multidrug-resistant (MDR) strains accounted for 90.51% (143/158), and 6 strains were only resistant to sulfisoxazole. Furthermore, 40% and 30% of the strains had sul3 and sul1 genes; all strains were sensitive to polymixin B, and no strains had the mcr-1 gene. Among the 8 S. enterica strains (5.59%), 14 genes were identified, with the β-lactam gene bla TEM-1 expressed in all MDR isolates. Only the floR and tetB genes were consistent with the PCR results for the predicted drug resistance genes in Salmonella-NMGS9 strains. Conclusions This study is the first to determine the prevalence, antimicrobial resistance, and genetic characteristics, of Salmonella spp. isolated from large-scale cattle farms in Inner Mongolia, China. Monitoring the prevalence, resistance gene expression, and distribution of Salmonella on large-scale cattle farms in Inner Mongolia is vital for understanding the extent and trends in foodborne pathogen resistance in China.